Efektivitas Penggunaan Media Powerpoint dalam Pembelajaran Daring pada Mata Pelajaran IPS Siswa SMP - Raldy Wiliam Pasuhuk; Andrew Christian Aseng; Lanemey Brigitha Pandeirot (Journal on Education, 2023)
Microsoft (MS) PowerPoint is one of the learning tools that is frequently used in learning activities at SMP Labor UNKLAB. This study was conducted to find out the effectiveness of using PowerPoint media in online classes for Social Sciences (IPS) subject at SMP Labor UNKLAB. This research is a quantitative descriptive study using mean value and percentage to measure the effectiveness of PowerPoint in online learning. A total of 64 students of grade IX participated in this study by filling out a questionnaire which was distributed online using Google Form. The results of data processing using statistical and descriptive frequency methods found that MS PowerPoint was proven to be effective in its use in online learning, especially in social studies subjects. The results of the study support several previous studies related to this topic as well as provide information and input to several parties regarding the use of MS PowerPoint in online learning.